2016
DOI: 10.15414/raae.2016.19.01.03-12
|View full text |Cite
|
Sign up to set email alerts
|

The integration of pigmeat markets in the eu evidence from a regular mixed vine Copula

Abstract: The objective of this work is to investigate the degree of integration of national pigmeat markets in the EU. This is pursued using monthly wholesale prices from seven major markets and the statistical tool of mixed R-vine copulas. The empirical results suggest that the markets considered do not constitute a great pool in which prices move, boom, and crash together. The markets of Belgium, Germany, and the Netherlands exhibit a higher degree of integration relative to the others, whereas the Italian market exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 5 publications
0
17
0
5
Order By: Relevance
“…It is therefore essential that the conditional measures of co‐movement are presented in empirical studies. When under the condition of a third price, the co‐movement between two prices is found to decrease (increase), it is concluded that their interdependence was magnified (clouded) due to the third price (Aguiar‐Conraria and Soares ; Grigoriadis et al ). Hence R‐Vines may reveal aspects of co‐movement that standard bivariate copulas cannot capture.…”
Section: Measuring Dependencementioning
confidence: 99%
See 4 more Smart Citations
“…It is therefore essential that the conditional measures of co‐movement are presented in empirical studies. When under the condition of a third price, the co‐movement between two prices is found to decrease (increase), it is concluded that their interdependence was magnified (clouded) due to the third price (Aguiar‐Conraria and Soares ; Grigoriadis et al ). Hence R‐Vines may reveal aspects of co‐movement that standard bivariate copulas cannot capture.…”
Section: Measuring Dependencementioning
confidence: 99%
“…Copulas provide an effective way to approach price transmission and thus to assess market integration. They possess certain attractive attributes: they allow the joint behaviour of stochastic processes to be modelled independently of their marginal distributions; they need not assume that marginal distributions belong to the same family; they are suitable for capturing both linear and non‐linear co‐movements; and they provide information about the degree as well as the structure of the co‐movement (Fermanian and Scaillet ; Grigoriadis et al ). Thus, copulas are highly appropriate for analysing co‐movement between stochastic processes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations